Clinical and immunopathological spectrum of immunoglobulin M pemphigoid: a multicenter case series - Yilmaz, Osman K.; Goletz, Stephanie; Hammers, Christoph M.; Boch, Katharina; Zeidler, Claudia; Wiegmann, Henning; Bergmann, Estelle; Lari, Tina Rastegar; Dikmen, Onur; Häring, Nina; Strohal, Robert; Kleinheinz, Andreas; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2025)
Background and Objectives Pemphigoid diseases are primarily mediated by IgG or IgA autoantibodies against the cutaneous basement membrane zone (BMZ). Although recent observations suggest the existence of exclusively IgM-mediated pemphigoid disease, a larger study is lacking. Patients and Methods This prospective multicenter study included ten patients with exclusive IgM deposition along the BMZ by direct immunofluorescence (IF). Circulating IgM was detected by indirect IF and immunoblotting with recombinant BP180. Results The cohort, four females and six males with a median age of 77 years, presented predominantly with prurigo-like lesions without blisters and mucosal involvement. Sera from nine patients demonstrated linear IgM labeling the blister roof of human salt-split skin by indirect IF. Four patients yielded IgM reactivity against BP180, but none against BP230. In none of the controls (n = 100), anti-BMZ IgM was seen by direct IF. 1/30 and 3/60 controls with or without pruritic non-pemphigoid diseases revealed serum IgM reactivity against the BMZ, respectively. Conclusions IgM pemphigoid is characterized by exclusive tissue-bound anti-BMZ IgM, serum anti-BMZ IgM reactivity with BP180 as main target antigen, a predominantly non-bullous clinical phenotype, absence of mucosal involvement, and a rather mild disease course. Our findings indicate that IgM pemphigoid may represent a distinct entity.